2008
DOI: 10.1038/gene.2008.59
|View full text |Cite
|
Sign up to set email alerts
|

Replication of KIAA0350, IL2RA, RPL5 and CD58 as multiple sclerosis susceptibility genes in Australians

Abstract: A recent genome-wide association study (GWAS) conducted by the International Multiple Sclerosis Genetics Consortium (IMSGC) identified a number of putative MS susceptibility genes. Here we have performed a replication study in 1134 Australian MS cases and 1265 controls for 17 risk-associated single nucleotide polymorphisms (SNPs) reported by the IMSGC. Of 16 SNPs that passed quality control filters, four, each corresponding to a different non-human leukocyte antigen (HLA) gene, were associated with disease sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
81
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 27 publications
5
81
0
1
Order By: Relevance
“…5,6 Only recently, with analysis of very large cohorts, non-human leukocyte antigen MS genes are starting to be unambiguously identified. [7][8][9][10][11][12][13][14] Another important concept is the sharing of risk genes between inflammatory diseases, 15 as now demonstrated for type 1 diabetes and MS genes. 12 Therefore, cross-disciplinary genetics may be rewarding.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Only recently, with analysis of very large cohorts, non-human leukocyte antigen MS genes are starting to be unambiguously identified. [7][8][9][10][11][12][13][14] Another important concept is the sharing of risk genes between inflammatory diseases, 15 as now demonstrated for type 1 diabetes and MS genes. 12 Therefore, cross-disciplinary genetics may be rewarding.…”
Section: Introductionmentioning
confidence: 99%
“…All were included in the study as part of the tagging SNP set, except rs6498169, previously reported to be associated with MS and anti-CCP-negative rheumatoid arthritis. 2,6,8,11 The most significantly associated SNP, rs12923849 has previously showed some degree of association with T1D. 1 The other three top hits in our screening phase; rs9934231, rs6498168 and rs7206912 have not previously been reported to be associated in MS or other autoimmune diseases.…”
Section: Screening Phasementioning
confidence: 89%
“…[1][2][3] Multiple replication and candidate gene studies have verified this region as being disease associated in T1D and MS, and association with CLEC16A has also been found in anti-cyclic citrullinated peptide (CCP) negative rheumatoid arthritis, juvenile idiopathic arthritis, Addison's disease and NOD2-negative Crohn's disease. [4][5][6][7][8][9] The association of CLEC16A SNPs across multiple immune-mediated diseases and the observation that the gene is almost uniquely expressed on immune cells, make a common effect on autoimmunity likely. The CLEC16A protein belongs to the C-type lectin family whose immune functions include differentiation of self versus non-self glycoproteins and the induction of the appropriate immune response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies find association between MS and this gene in Caucasian populations. [8][9][10][11][12][13] The method using case-control data selects a minimal subset of seven associated SNPs, which reduces to three SNPs when using family data. The second step shows that none of these SNPs is causal, and that the association signal is due to at least two different ungenotyped variants in the region.…”
Section: Introductionmentioning
confidence: 99%